Effect of some parameters in the synthesis of silver nanoparticles and its evaluation as antimicrobes - Chowdhury, Silvia; Yusof, Faridah; Sulaiman, Nadzril; Faruck, Mohammad Omer (Kulliyah of Engineering, International Islamic University Malaysia, 2016)

(untitled)
Metallic silver (Ag) and some Ag compounds have long being used to fight microbial infection even before the emergence of antibiotics. But lately, one of the problems facing the medical world is the occurrence of drug resistance microbes. Therefore, actions must be taken to reduce the problem, one of which is to continue studies to develop new drug, either synthetic or natural. The ultimate goal is to offer appropriate and efficient antimicrobial drug to the patient. In this regard, with the advent of nanotechnology, it is now possible to synthesize nano scale Ag which can be used in diverse medical applications. The aim of this study is to investigate the effect of some important parameters towards the production of high yield Ag nanoparticles (AgNPs) from silver salts using reducing agent. Based on the analyses by its yellow color, UV-vis in the range of 350 to 420 nm wavelength and surface plasmon resonance (SPR) at 420 nm, AgNPs produced were estimated to be in the range of 10 to 15 nm in diameter. Out of five parameters tested, such as silver nitrate (AgNO3) concentration, stirring time, pH of aqueous AgNO3, tri-sodium citrate concentration and reaction time, results showed that all factors except stirring time affects the production. Characterization of AgNPs, carried out using transmission electron microscope (TEM), showed that the synthesized AgNPs were spherical with diameters less than 15 nm. Antimicrobial activity assays, carried out against selected microbes, namely Aspergillus niger, Microsporum canis and Staphylococcus aureus showed various degree of potencies